Chronic retropharyngeal abscess - Chowdhury, M Alamgir; Yasmeen, Naseem; Tshering, Phub (Bangladesh Journal of Otorhinolaryngology, 2012)
Introduction: Chronic retropharyngeal abscess can occur in the adults as well as in children. It is usually due to tuberculous infection of the cervical spine as the pus directly spreads through the anterior longitudinal ligament into the retropharyngeal space. Case report: We report a case of chronic retropharyngeal abscess in a 60-year-old woman who presented with throat pain and dysphagia. On examination there was bulging of the posterior pharyngeal wall and also right sided neck swelling. She was treated by external drainage of abscess under local anaesthesia and she recovered well with anti-tubercular drugs DOI: http://dx.doi.org/10.3329/bjo.v18i2.12032 Bangladesh J Otorhinolaryngol 2012; 18(2): 242-244